Chronic toxicity of the antiepileptic carbamazepine on the clam ruditapes philippinarum - Almeida, Ângela (2017)
The impacts of carbamazepine (CBZ) on aquatic organisms are yet notwell investigated. The present study aimed to better understand the chronic effects of environmentally relevant concentrations of CBZ. The experiment was performedby exposing the filter feeding clamRuditapes philippinarum to 0.00, 0.03, 0.30, 3.00 and 9.00 μg/L, during 28 days. To assess the chronic toxicity of the drug a battery of biomarkers related with health status and oxidative stress was applied. In order to quantify CBZ in the clam's tissues and in water samples ELISA was used. The present study showed three types of responses on the clams after a chronic exposure to CBZ. For control condition and the lower concentrations (0.03 and 0.30 μg/L) a “similar” metabolic state was observed and the most efficient antioxidant status leading to the elimination of reactive oxygen species formed during themetabolismof CBZ. The concentration of 3.00 μg/L seemed to be a “threshold” concentration, beyond which the concentration levels of CBZ began to exert a toxic effect, compromising the activity of biotransformation and antioxidant enzymes, with notorious effects at the highest CBZ concentration (9.00 μg/L). CBZ also seemed to alter the energy-related responses, especially the glycogen and electron system responses, revealing a slowdown in metabolism at the higher exposure concentrations (3.00 and 9.00 μg/L). Overall, the present study demonstrated that the higher CBZ concentrations can lead to the impairment of antioxidant enzymes compromising the neutralization of reactive oxygen species, and thus the ability to cope with oxidative stress.